Clinical rather than genetic factors predict hepatic cyst burden and growth in autosomal dominant polycystic kidney disease: a cohort study of 332 genotyped patients - Keiji Takahashi; Haruna Kawano; Tomoki Kimura; Yan Lu; Satoru Muto; Shigeo Horie (Clinical and Experimental Nephrology, 2026)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) frequently involves polycystic liver disease (PLD), which can impair quality of life. While genotype strongly predicts renal outcomes, determinants of hepatic cyst burden and progression remain unclear. Methods We retrospectively analyzed 332 genotyped patients with ADPKD. Total liver volume was quantified on serial CT to calculate height-adjusted TLV (HtTLV) and annual percentage growth (ΔHtTLV/year). To reduce baseline dependency inherent to ratio-based outcomes, we additionally evaluated a log-transformed growth metric (log[HtTLV2/HtTLV1]/year). Associations with demographic, clinical, and medication factors were examined using multivariable linear regression. Results Genotype was not associated with hepatic cyst prevalence, baseline HtTLV, or growth. Greater hepatic cyst burden (HtTLV) was independently associated with female sex, Mayo class C–E, smoking history, and higher BMI. For progression, calcium channel blocker (CCB) use remained independently associated with higher growth in both ΔHtTLV/year and log-transformed models, whereas other antihypertensive classes were not. Baseline HtTLV was strongly associated with subsequent growth across models. Conclusions In this cohort, clinical factors were more closely associated with PLD burden and progression than genotype. CCB exposure was consistently associated with higher hepatic growth metrics; however, because residual confounding by indication remains possible, causality cannot be inferred. Nevertheless, this association represents a clinically important hypothesis that should be evaluated in future prospective studies.